Creating an integrated information retrieval system Scientific and Technical Library of National Aviation University using existing bibliographic databases - Іванкевич, О. В.; Вахнован, В. Ю. (Problems of Informatization and Control, 2013)
The rapid development of the information space of the world and Ukraine and increase the number ofpaper and electronic documents in libraries causes problems effectively work with documents, whichentails a significant increase in the time to find the desired document. The problem can be solvedthrough the use of automation of the search based on the use of computer systems. The work isdedicated to the creation of an information retrieval system, linked to a bibliographic database andsystem of informing users of the library institution of higher education and the availability of seatsconservation literature. The existing mechanisms for receiving, storing and processing data andfeatures improve productivity of library computer systems.